Dakwah Media Radio Jakarta Islami Center (JIC) di Era Digital - Choiri, Moh. Amir; Yosepin, Pipin (Palita: Journal of Social Religion Research, 2024)
The development and advancement of today's technological world have helped overcome various obstacles in life.  In the digital era, the fulfilment of information needs is a necessity that cannot be denied. Da'wah through radio media radio owned by the DKI Jakarta government is one of the radios that broadcast Islamic da'wah.  Radio as a broadcasting media also has a role in its da'wah mission. Like Radio Jakarta Islamic Center by implementing da'wah programs in its broadcast content. It's broadcast content. This writing aims to describe the role of da'wah through JIC radio media in the digital era. Researchers conducted in-depth interviews with interviewing informants including the head of the JIC radio da'wah program, the head of JIC radio, and two JIC radio broadcasters.JIC, and two JIC radio broadcasters. The data analysis technique is carried out by the results showed that the role of JIC radio media da'wah in the digital era is increasingly enhanced following the development of the JIC radio program. The digital era is increasingly being improved by following technological developments and the use of social media such as YouTube and others. Radio JIC uses some creative strategies when there is media convergence to improve the quality of broadcasters and can to improve the quality of broadcasters and can strive for broadcasters to present material well. Keywords: Digital Era, Da'wah, Media Convergence, Radio JIC